EDUCATION AND APPLICATION OF PROCESS COSTING FOR HOME INDUSTRY ACTORS IN DETERMINING COMPETITIVE PRODUCT PRICES - Nur Afni Yunita; Nurhasanah; Rany Gesta Putri; Sri Mulyati; Muhammad Yusra (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This Community Service Activity (PKM) was carried out to improve the understanding of home industry players in applying the process costing method as the basis for calculating production costs and determining competitive selling prices. A lack of understanding of cost allocation leads to inaccuracies in pricing and business performance measurement. Through training and mentoring activities, partners were trained to systematically identify, calculate, and accumulate production costs and compile simple financial reports. The results of the activities showed an increase in the partners' ability to manage costs, use resources efficiently, and accurately set product prices. The application of process costing has proven to support more professional, efficient, and competitive business management.